2007
DOI: 10.1097/01.aog.0000247291.00155.88
|View full text |Cite
|
Sign up to set email alerts
|

Vesicovaginal Fistula Formation After Cervical Cerclage Mimicking Premature Rupture of Membranes

Abstract: Obstetricians should recognize that cerclage placement may result in unusual urinary tract injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Two VVFs occurred after cervical cerclage, as previously described in the literature. 21 The risk of this procedure is usually underestimated, and deep or high placement of the cervical suture should, therefore, be avoided. Furthermore, vaginal leakage after cervical cerclage should not be assumed to be the rupture of membranes and must be thoroughly investigated to rule out urogenital fistula.…”
Section: Discussionmentioning
confidence: 99%
“…Two VVFs occurred after cervical cerclage, as previously described in the literature. 21 The risk of this procedure is usually underestimated, and deep or high placement of the cervical suture should, therefore, be avoided. Furthermore, vaginal leakage after cervical cerclage should not be assumed to be the rupture of membranes and must be thoroughly investigated to rule out urogenital fistula.…”
Section: Discussionmentioning
confidence: 99%
“…1,14 It remains unclear whether dissection of the vesicovaginal space may be protective against inadvertent suture placement into or through the bladder wall, but cystoscopy after the cerclage placement may be beneficial to identify stitch placements that involve the bladder.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 There are multiple complications of cerclage reported in the literature with most occurring in the antepartum or intrapartum periods. 3 Remote sequelae and genitourinary injury because of cerclage placement are rare.…”
mentioning
confidence: 99%
“…Vesicovaginal fistulas are usually related to gynecologic surgery, most commonly hysterectomy in developed countries 5 . Recently, some cases have reported that vaginal foreign body 11,12 or cervical cerclage 13 cause vesicovaginal fistulas. Most authors who reported these cases suggest chronic irritation and inflammation, not direct penetration, would cause the complication.…”
Section: Discussionmentioning
confidence: 99%